1990
DOI: 10.1210/jcem-71-1-40
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Antibodies Blocking Thyrotropin EffectIn Vitroin Patients with Euthyroid or Hypothyroid Autoimmune Thyroiditis*

Abstract: Autoantibodies blocking the TSH-dependent production of cAMP in thyroid cells (TSH-BAb) have been described in atrophic thyroiditis (AT; idiopathic myxedema) and in neonates with transient hypothyroidism, but their incidence in autoimmune thyroiditis in relation to thyroid status remains to be completely established. To this purpose TSH-BAb were evaluated in a group of 140 consecutive patients with autoimmune thyroiditis, which included 26 cases of AT and 114 subjects with goitrous Hashimoto's thyroiditis (HT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 26 publications
0
40
1
Order By: Relevance
“…DELFIA free thyroxine (FT4) and DELFIA hTSH kits were purchased from Kabi Pharmacia (Wallac Oy, Turku, Finland). The interassay coefficients of variation were 11% (6-8 pmol/L), 7% (16)(17)(18)(19) pmol/L), and 8% (43-53 pmol/L) for the fT4 assay, and 6% (0.77-1.03 mU/L), 4% (4.3-5.7 mU/L), and 3% (22)(23)(24)(25)(26)(27)(28)(29)(30) (20,21). For as¬ says, the cells were subcultured onto 12-well plates and grown to confluence.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…DELFIA free thyroxine (FT4) and DELFIA hTSH kits were purchased from Kabi Pharmacia (Wallac Oy, Turku, Finland). The interassay coefficients of variation were 11% (6-8 pmol/L), 7% (16)(17)(18)(19) pmol/L), and 8% (43-53 pmol/L) for the fT4 assay, and 6% (0.77-1.03 mU/L), 4% (4.3-5.7 mU/L), and 3% (22)(23)(24)(25)(26)(27)(28)(29)(30) (20,21). For as¬ says, the cells were subcultured onto 12-well plates and grown to confluence.…”
Section: Methodsmentioning
confidence: 95%
“…Results were expressed as a percentage of inhibition (25) TBAb levels >25 were regarded as being positive. Both TSAb and TBAb levels were determined for all samples concurrently.…”
Section: Tsab and Tbab Assaysmentioning
confidence: 99%
“…On the other hand, it has been shown that over 20% of patients with goitrous Hashimoto's disease, who were initially in a hypothyroid state, may recover normal hormonal thyroid function under L-T4 therapy [15]. Furthermore, it has been re ported that this newborn thyroid function may persist for more than 1 year after L-T4 therapy is discontinued and seems to be related to a spontaneous decrease in serum TSH-blocking Ab levels [16][17][18][19], but not to thyroid status. In contrast, it has been recently shown in hypothyroid patients with goitrous Hashimoto's thyroiditis that both mean plasma TSH level and prevalence of serum TSH-R Ab decreased under L-T4 therapy and increased again after cessation of such a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated in these patients that the suppression of TSH secretion by thyroid hormone during antithyroid drug therapy in duced a more important decrease in plasma TSH-R Ab levels than that observed when antithyroid drug treat ment was given alone [13,14]. On the other hand, it has been demonstrated in patients with goitrous Hashimoto's thyroiditis that the hypothyroid state could be related to TSH-R Ab blocking the action of TSH at the gland level [16][17][18][19], Furthermore, it has been reported that patients with goitrous Hashimoto's thyroidits in an initially hypo thyroid state may recover a normal thyroid function dur ing L-T4 therapy [ 15]. This newborn normal thyroid func tion seems to be related to a spontaneous decrease in TSH-R Ab [ 16].…”
mentioning
confidence: 99%
“…TSAb, after the interaction with the receptor, increase cAMP accumulation causing goiter and hyperthyroidism (2,3). In atrophic thyroiditis (AT), thyroid-stimulating blocking antibodies (TSHBAb) are TSH antagonists, inhibiting TSH binding or TSH-increased cAMP levels causing thyroid atrophy and hypothyroidism (2,(4)(5)(6). The different activities of TSAb and TSHBAb suggest they might interact with different epitopes on the TSHr (2).…”
Section: Introductionmentioning
confidence: 99%